Evaluating the Economic and Ecological Importance of Traditional Fruit Trees in Uttarakhand - Maneesha Singh (International Journal of Land, 2024)
This study investigates the distribution, morphological characteristics, phyto-constituents, and conservation practices of traditional fruit trees in Uttarakhand, India. The region, characterized by its mountainous terrain and diverse climatic conditions, hosts a variety of fruit species, including apple, pear, peach, plum, khumani, walnut, mango, litchi, malta, santra, lemon, aonla, guava, and pomegranate. Data on morphological traits were collected from hilly and valley areas, emphasizing their traditional importance and nutraceutical values. Furthermore, the study explores local conservation strategies aimed at sustaining these vital resources. Findings indicate a growing recognition among local communities of the nutritional benefits offered by wild edible fruit species, contributing to food security and aligning with sustainable development goals, particularly Zero Hunger.
Keywords: Conservation practices; Food security; Morphological characteristics; Nutraceutical values; Phyto-constituents; Traditional fruit trees; Wild edible fruits; sustainable development; uttarakhand